PENGARUH PENGETAHUAN KEWIRAUSAHAAN, SELF EFFICACY DAN LINGKUNGAN SOSIAL TERHADAP INTENSI BERWIRAUSAHA MAHASISWA UNIVERSITAS ABC TANGERANG - Handayani, Ni Putu Cetana Sri; wijaya, Shierli (Jurnal Nusa Manajemen, 2025)
The increasing competition in the labor market has led to a rise in unemployment, particularly among university graduates. Although increasing the number of entrepreneurs could be a solution, entrepreneurial intentions remain low among students. This study aims to analyze the influence of entrepreneurial knowledge, self efficacy, and social environment on the entrepreneurial intentions of students at Universitas ABC Tangerang. The research method used is quantitative, with a population consisting of ABC University students from the 2020 and 2021 cohorts who have completed the entrepreneurship course. The total population is 468 students, and the research sample comprises 216 students. The sampling technique employed is probability sampling, with data collected through the distribution of questionnaires, which were then analyzed using the SPSS statistical software version 30. The results show that: 1) Entrepreneurial knowledge has a positive and significant effect on entrepreneurial intentions among students at Universitas ABC Tangerang, 2) Self-efficacy has a positive and significant effect on entrepreneurial intentions among students at Universitas ABC Tangerang, 3) Social environment has a positive and significant effect on entrepreneurial intentions among students at Universitas ABC Tangerang, 4) Entrepreneurial knowledge, self efficacy, and social environment have a positive and significant simultaneous effect on entrepreneurial intentions among students at Universitas ABC Tangerang. The findings of this study are expected to provide valuable insights for the university in enhancing students' entrepreneurial intentions amid the increasingly competitive job market.